Crop Health Management: Perspectives in IPM - S. Bhagat; A. Birah; C. Chattopadhyay (International Journal of Economic Plants)
Integrated pest management (IPM) has evolved over time through integrated crop production to integrated farming system targeted at improved crop health. IPM is knowledge intensive, requires holistic approach, expert advice, timely decision making and actions on fast track. Recent interactions with the farming communities revealed that 93% of the farmers in India had adopted chemical control, 51% farmers get their plant protection advice from dealers, while 22% from extension officials and majority of the farmers (73%) initiate the plant protection based on the appearance of the pest, irrespective of their crop stage, damage relationships and their population. Programmes on training of both the extension workers and farmers in the Integrated Pest Management (IPM) were started throughout the country. In fact, the Government of India had adopted IPM as a cardinal principle of plant protection in 1985. Even though, adoption of IPM has not been encouraging as biopesticides capture hardly 2% of the agrochemical market.  Biological control is also a very effective component of crop protection. Due to public awareness about the hazards related to use of chemical pesticides, there has been a lot of interest generated for use of eco-friendly strategies targeted at management of crop pests. For this purpose, bio-pesticides could be a cost-effective, eco-friendly and sustainable option.